Anticonstriction Effect of MCA in Rats by Danggui Buxue Decoction - Guo, Ying; Zhang, Yating; Hou, Ya; Guo, Pengmei; Wang, Xiaobo; Zhang, Sanyin; Yang, Peng (Frontiers in Pharmacology, 2021)
Objective: Danggui Buxue decoction (DBD), consisting of Angelicae Sinensis Radix (ASR) and Astragali Radix (AR), is a famous prescription with the function of antivasoconstriction. This study intends to probe its mechanisms on the relaxation of the middle cerebral artery (MCA). Methods: Vascular tension of rat MCA was measured using a DMT620 M system. First, the identical series of concentrations of DBD, ASR, and AR were added into resting KCl and U46619 preconstricted MCA. According to the compatibility ratio, their dilatation effects were further investigated on KCl and U46619 preconstricted vessels. Third, four K+ channel blockers were employed to probe the vasodilator mechanism on KCl-contracted MCA. We finally examined the effects of DBD, ASR, and AR on the vascular tone of U46619-contracted MCA in the presence or absence of Ca2+. Results: Data suggested that DBD, ASR, and AR can relax on KCl and U46619 precontracted MCA with no effects on resting vessels. The vasodilator effect of ASR was greater than those of DBD and AR on KCl-contracted MCA. For U46619-contracted MCA, ASR showed a stronger vasodilator effect than DBD and AR at low concentrations, but DBD was stronger than ASR at high concentrations. Amazingly, the vasodilator effect of DBD was stronger than that of AR at all concentrations on two vasoconstrictors which evoked MCA. The vasodilator effect of ASR was superior to that of DBD at a compatibility ratio on KCl-contracted MCA at low concentrations, while being inferior to DBD at high concentrations. However, DBD exceeded AR in vasodilating MCA at all concentrations. For U46619-constricted MCA, DBD, ASR, and AR had almost identical vasodilation. The dilation of DBD and AR on KCl-contracted MCA was independent of K+ channel blockers. However, ASR may inhibit the K+ channel opening partially through synergistic interactions with Gli and BaCl2. DBD, ASR, and AR may be responsible for inhibiting [Ca2+]out, while ASR and AR can also inhibit [Ca2+]in. Conclusion: DBD can relax MCA with no effects on resting vessels. The mechanism may be related to ASR’s inhibition of KATP and Kir channels. Meanwhile, the inhibition of [Ca2+]out by DBD, ASR, and AR as well as the inhibition of [Ca2+]in by ASR and AR may contribute to dilate MCA.